Pengaruh Media Digital Dalam Memberdayakan Kemampuan Berpikir Kritis Pada Pembelajaran IPA di Sekolah Dasar - Salsabilah Ramadanis; Ibnu Muthi (Lembaga Pengembangan Kinerja Dosen, 2024)
Students' critical thinking skills in natural science learning in elementary schools are not optimal because teachers have not used learning media that suit the characteristics of students and teaching materials. The aim of this research is to describe digital media innovations in empowering critical thinking skills in natural science learning in elementary schools. This research uses a literature review research design with a qualitative approach. The data in this research is secondary data. Data collection techniques use literature studies related to books, national journals and international journals according to the research focus. The data analysis technique is a content analysis technique.